Inequality in survival of people with head and neck cancer: Head and Neck 5000 cohort study. Issue 4 (8th January 2021) - Ingarfield, Kate; McMahon, Alex D.; Hurley, Katrina; Toms, Stu; Pring, Miranda; Thomas, Steve J.; Waylen, Andrea; Pawlita, Michael; Waterboer, Tim; Ness, Andy R.; Conway, David I.
Abstract: Background: Explanations for socioeconomic inequalities in survival of head and neck cancer (HNC) patients have had limited attention and are not well understood. Methods: The UK Head and Neck 5000 prospective clinical cohort study was analyzed. Survival relating to measures of socioeconomic status was explored including area‐based and individual factors. Three‐year overall survival was determined using the Kaplan–Meier method. All‐cause mortality was investigated via adjusted Cox Proportional Hazard models. Results: A total of 3440 people were included. Three‐year overall survival was 76.3% (95% CI 74.9, 77.7). Inequality in survival by deprivation category, highest education level, and financial concerns was explained by age, sex, health, and behavioral factors. None of the potential explanatory factors fully explained the inequality associated with annual household income or the proportion of income of benefits. Conclusion: These results support the interventions to address the financial issues within the wider care and support provided to HNC patients.